A Tale of Two Legacies: Career Narratives of the Black Family Business. (January 2016) - Jackson, P. R.
The career development of Blacks has been neglected in literature for years. The focus on the Black family business and how this dynamic creates family career legacies, which are perpetuated through generations, adds to this body of literature. In the collection of career stories from members of two Black family businesses, this article sought to understand how Blacks made meaning of the events that influenced their career decisions, constructing these events into their involvement in the business and thereby maintaining their family career legacy. Through narrative analysis, findings indicated family career legacies were created through specific career opportunities available as a result of being Black and a desire to discontinue struggle and career hardships for future generations.